Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5897/ajb11.393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GR24, a synthetic analogue of strigolactones, on gene expression of solopathogenic strain of Sporisorium reilianum

Abstract: Sporisorium reilianum f.sp zeae, a basidiomycetous fungus belonging to Ustilaginaceae, is the causal agent of maize head smut. Its pathogenicity is initiated by fusion of two compatible sporidia which give rise to the formation of a dikaryotic pathogenic hyphe. In addition, pathogenic dimorphic diploid strains called solopathogens can be formed where no mating occurs. Strigolactones are the trace molecules in plant root exudates perceived by some fungi at subnanomolar concentrations that have been implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(C) Pathogenic fungi interactions. In the preliminary data, SLs were not found to induce hyphal branching or respiration processes of the examined plant pathogens [30,34]. Even though there is no clear evidence that SLs are or are not a part of a host-pathogen signaling relation, it is an area that is interesting and undoubtedly tempting to explore, with some indications that SLs may be engaged in this process as signals preventing infection by promoting AM symbiosis.…”
Section: Strigolactones and Ectomycorrhizal Fungi (Ecm)mentioning
confidence: 88%
See 2 more Smart Citations
“…(C) Pathogenic fungi interactions. In the preliminary data, SLs were not found to induce hyphal branching or respiration processes of the examined plant pathogens [30,34]. Even though there is no clear evidence that SLs are or are not a part of a host-pathogen signaling relation, it is an area that is interesting and undoubtedly tempting to explore, with some indications that SLs may be engaged in this process as signals preventing infection by promoting AM symbiosis.…”
Section: Strigolactones and Ectomycorrhizal Fungi (Ecm)mentioning
confidence: 88%
“…Another study conducted in 2001 by Martinez et al [33] showed that fractions of maize root exudates could induce the transition of yeast to a hyphal form. In later research, Sabbagh [34] analyzed the transcriptome expression of a haploid strain of S. reilianum using different concentrations of GR24, and most of the expressed sequence tag (EST) after SL application was related to genes taking part in cell respiration processes. Exogenous GR24 effects on Ustilago maydis, a fungus causing smut on maize, induced genes involved in cell respiration at 1 h, increased the process at 5 h, and stopped it at 8 h postsupplementation; further analysis of cells induced at 8 h showed the lack of any candidate gene transcripts [34].…”
Section: Strigolactones and Pathogenic Fungimentioning
confidence: 99%
See 1 more Smart Citation